(untitled) (Prithvi Academic Journal, 2019)
Sumnima, a novel written by Bishweshwar Prasad Koirala (BP Koirala in short), has raised voice for social integration through harmonious relationship among the ethnic groups. But it is read as the presentation of binary between Aryan and Kirat cultures, highlighting differences in belief systems, rites, rituals, and day to day lifestyle that create misunderstanding, conflict, and problems among the people of different cultural groups. The main objective of studying the novel, in this article, is to find how the novelist offers an opportunity to the readers to realize the ideas and benefits of harmony among the divergent ethnic communities living in Nepal or elsewhere through understanding differences and celebrating the diversity. Theoretical insights of ethnicity have been used to analyze the primary text. The article argues, taking the reference of the novel, that ethnic misunderstandings and conflicts can be solved by understanding cultural norms and values of others. The article also examines and analyzes how the relations without understanding cannot prosper even within the same ethnic group but love and understanding makes the life beautiful no matter which tribe or ethnicity the people belong to. The implicit intention of the novelist in the novel is that in a culturally diverse society, mutual understanding, compromise, and respect of difference make the society a ‘salad bowl’ that works better than trying to make it a ‘melting pot’.